Impact of raised beds on surface runoff and soil loss in Alfisols and Vertisols - Garg, K. K.; Anantha, K. H.; Dixit, S.; Nune, R.; Venkataradha, A.; Wable, P.; Budama, N.; Singh, R. (Elsevier, 2022)
Hydrological monitoring is crucial to designing agricultural water management (AWM) interventions. This study characterizes the soil hydraulic properties of Alfisols and Vertisols and develops rainfall-runoff-soil loss relationships through long-term hydrological monitoring. Two types of landform management techniques, i.e., raised bed and flat bed, were followed in three paired watersheds of 2–5 ha, characterized by deep Vertisols, medium deep Vertisols and Alfisols. Surface runoff and soil loss were monitored at the outlet of the respective watersheds for 8–12 years. In addition, 29 infiltration tests were conducted using a tension disc infiltrometer by applying a suction of −150 mm, −100 mm, −50 mm, and −20 mm. Soil macro porosity and hydraulic conductivity in the raised bed landform were found to be almost double those in the flat beds at −50 mm suction head in both the soil types. Saturated hydraulic conductivity was found higher in Alfisols compared to Vertisols; however, less runoff was generated in Vertisols compared to Alfisols. This phenomenon is largely explained by the high water storage capacity of Vertisols. Runoff generated from both the soils was less than 2% of total rainfall (<500 mm) received in dry years. In normal years (600–900 mm), runoff coefficient for Vertisols ranged from 7–11% of total rainfall compared to 16–17% in the case of Alfisols. However, runoff generated from fallow land was 17% in deep Vertisols due to higher soil moisture content and limited available storage compared to the cropped land. The raised bed method reduced surface runoff by 15–20 mm in Alfisols compared to 35–40 mm in Vertisols. Runoff from the raised beds was significantly lower during light and moderate intensity rainfall compared to the flat bed method; however, this difference was not significant during events of high and very high intensity rainfall. In addition, raised beds reduced soil loss by 30–60% compared to flat beds. The results of this study are useful in designing evidence-based AWM strategies under rainfed conditions.